Impact of the Coronavirus Disease 2019 Epidemic on Sea Freight - Luypornsuksawang, Tharaya; Charoenwiriyakul, Chandej; Siriwattana, Srochinee; Suwannapirom, Suda (The Journal of Development Administration Research, 2023)
This study aimed to study 1) the impact of the coronavirus disease 2019 epidemic on Sea Freight and 2) ways to reduce the impact on Sea Freight in the coronavirus disease 2019 epidemic. This study was qualitative. The key informants consisted of representatives of ship-related companies or shipping line operators, affected import-export companies, and the import-export freight forwarding association, totaling 17 people selected by purposive sampling. The tools used were documentary research and in-depth interviews. Data analysis by content analysis The results showed that 1) the following: (1) Labor shortages from measures to prevent the spread of COVID-19, especially the lockdown; (2) The shortage of containers due to the lack of labor, containers were left in the port. (3) The freight rates increased. (4) Increased other costs; and 2) the guidelines to reduce such impacts should be implemented as follows: (1) the government should assist SMEs in terms of capital and trade facilitation and transport. (2) There should be an international forum to consider jointly solving problems in times of crisis, such as the COVID-19 outbreak; (3) Information technology should be applied to enhance the efficiency of port management. (4) The port capacity should be increased to be able support the increased volume of goods. To reduce port congestion and congestion, (5) concrete and legally binding measures and aid mechanisms should be in place.